KUALITAS PELAYANAN ROOM BOY DI HOTEL GRAND ZURI PEKANBARU RIAU - Nia Audina; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The success of a company is influenced by the quality of service employees. So from a company must increase customer satisfaction, and that must be done is to improve the quality of service (service quality) is real. This research is about the quality of roomboy service in grand zuri hotel Pekanbaru. This study aims to determine the response of guests to the dimensions of service quality roomboy in the hotel Grand Zuri Pekanbaru. The sample in this study was 100 people, taken from accidental sampling. This research uses quantitative descriptive method to classify the data and then compiled by using frequency. And data collection techniques in this study using interviews and questionnaires. By using Likert scale as a measuring tool. Based on the results obtained from the quality of service roomboy at the hotel Grand Zuri Pekanbaru is good. This is evidenced by the acquisition of the overall percentage.Keywords: Quality, Service, Dimension